PENGARUH TEST OF GROSS MOTOR DEVELOPMENT UNTUK MENINGKATKAN MOTORIK KASAR DALAM PERSPEKTIF HADIST PADA ANAK TINGKAT SEKOLAH DASAR - Susilowati, Endah; Lessy, Zulkipli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Physical education is an important component of education, not just an additional subject included in the school program. However, physical education is very important because it gives students the opportunity to be more actively involved in various movements related to sports. This is the reason why many students are attracted to physical learning as a way to channel their interests, develop their talents and channel their skills. Physical health is very important in the Islamic religion, and not taking care of it is the same as wronging yourself, because carrying out worship optimally requires good physical health. By using TGMD which includes twelve skills, including run, gallop, hop, leap, horizontal jump, slide, striking, dribble, catch, kick, and throw overarm, underhand roll. It is hoped that it can improve students' gross motor development. This field research uses quantitative research methods with Anava (One Path Analysis). Primary data consists of ten fifth grade students at SD Aisyiyah Lubuklinggau, and secondary data consists of heads. Therefore, it can be concluded that there is a significant relationship between the TGMD gross motor development test and the gross motor skills of fifth grade students in physical education, sports and health (PJOK). The results of the study also showed a significant relationship between the large motor development test (TGMD-2) and the gross motor skills of class V students at SD Aisyiyah Lubuklinggau. Keywords: elementary school, gross motor, TGMD